The SAMI Galaxy Survey: understanding observations of large-scale outflows at low redshift with EAGLE simulations. Issue 1 (9th September 2017) - Tescari, E.; Cortese, L.; Power, C.; Wyithe, J. S. B.; Ho, I.-T.; Crain, R. A.; Bland-Hawthorn, J.; Croom, S. M.; Kewley, L. J.; Schaye, J.; Bower, R. G.; Theuns, T.; et al.
Abstract: This work presents a study of galactic outflows driven by stellar feedback. We extract main-sequence disc galaxies with stellar mass 10 9 ≤ M ⋆ / M⊙ ≤ 5.7 × 10 10 at redshift z = 0 from the highest resolution cosmological simulation of the Evolution and Assembly of GaLaxies and their Environments (EAGLE) set. Synthetic gas rotation velocity and velocity dispersion (σ) maps are created and compared to observations of disc galaxies obtained with the Sydney-AAO (Australian Astronomical Observatory) Multi-object Integral field spectrograph (SAMI), where σ-values greater than 150 km s −1 are most naturally explained by bipolar outflows powered by starburst activity. We find that the extension of the simulated edge-on (pixelated) velocity dispersion probability distribution depends on stellar mass and star formation rate surface density (ΣSFR ), with low- M ⋆ /low-ΣSFR galaxies showing a narrow peak at low σ (∼30 km s −1 ) and more active, high- M ⋆ /high-ΣSFR galaxies reaching σ > 150 km s −1 . Although supernova-driven galactic winds in the EAGLE simulations may not entrain enough gas with T <10 5 K compared to observed galaxies, we find that gas temperature is a good proxy for the presence of outflows. There is a direct correlation between the thermal state of the gas and its state of motion as described by the σ-distribution. The following equivalence relations hold in EAGLE: (i) low-σ peak ⇔ disc of the galaxy ⇔ gas with T <10 5 K; (ii) high-σ tail ⇔ galactic winds ⇔ gas with T ≥10 5 K.